Digital finance and pawnshop lending growth: Evidence from Indonesia - Nafis Dwi Kartiko (Economic Military and Geographically Business Review, 2026)
Background: This study is situated within the rapid expansion of digital finance that has reshaped financial intermediation in emerging economies, while empirical attention has remained disproportionately focused on banks and fintech firms rather than collateral-based intermediaries. Prior literature emphasizes that digitalization reduces information frictions and transaction costs, yet evidence on how digital finance transforms pawnshop lending as an alternative credit channel remains limited. This study aims to examine the role of digital finance in driving pawnshop financing growth and to assess whether its impact varies across institutional types and financing distributions. Methods: The study adopts a quantitative empirical approach using monthly cluster-level data on pawnshops in Indonesia over an extended period. The analysis applies Robust Ordinary Least Squares to estimate average effects and Quantile Regression to capture heterogeneity across the financing distribution, with controls for customer scale, leverage structure, capital composition, and macro-financial conditions. Findings: The results indicate that greater digital finance intensity is associated with a statistically significant expansion of pawnshop financing, with stronger effects observed in government and conventional private pawnshops compared to sharia private pawnshops. Distributional estimates show that the positive effect of digitalization is most pronounced at low to medium financing levels, suggesting that digital finance primarily alleviates binding access constraints rather than amplifying already high lending volumes. Conclusion: Overall, the study demonstrates that digital finance complements rather than replaces collateral-based financial institutions by strengthening their intermediation capacity and expanding inclusive access to liquidity. The findings highlight digitalization as a structural mechanism supporting the resilience and evolution of traditional nonbank credit institutions in developing financial systems. Novelty/Originality of this article: This article provides original evidence on digital adaptation within pawnshop networks by integrating digital finance indicators into collateral-based lending models and employing a distributional econometric approach to reveal heterogeneous effects across institutional contexts.